Corporate Governance on Profitability - Alfian Bagus Millenianto (Eduvest - Journal of Universal Studies, 2024)
The purpose of this research is to examine the influence of Corporate Governance on company profitability. Corporate governance in this case is proxied by the size of the board of directors, independent board of commissioners and size of the audit committee. Meanwhile, the profitability variable is proxied by ROA (Return On Assets). This exploration was directed at 20 manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange for the period 2017 to 2021. Multiple linear regression was used as a statistical technique in this research. Research results show that the size of the Board of Commissioners has a positive and significant effect on profitability. The Independent Board of Commissioners has a positive and insignificant effect on Profitability. The size of the Audit Committee has a negative and insignificant effect on profitability.